2013
DOI: 10.1080/10408398.2011.563154
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies

Abstract: Food contagion with aflatoxins is the modern concern and has received a great awareness during the last few decades. The intermittent incidence of these toxins in agricultural commodities has negative role on the economy of the affected regions where harvest and postharvest techniques for the prevention of mold growth, are seldom practiced. Aflatoxins are difuranocoumarin derivatives produced by a polyketide pathway by the fungus Aspergillus flavus and Aspergillus parasiticus via polyketide pathway which are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 97 publications
0
87
0
3
Order By: Relevance
“…AF is synthesized by particular Aspergillus species, including A. flavus , A. parasiticus , A. nomius , and A. bombysis . Genetic investigations of the AF synthetic mechanism have shown AF synthetic fungi contain a specific gene cluster [1,2,3,4,5,6,7,8,9]. However, many non-toxigenic strains also have this gene cluster, although these clusters may have partial deletions and/or substitutions compared to those in AF synthetic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…AF is synthesized by particular Aspergillus species, including A. flavus , A. parasiticus , A. nomius , and A. bombysis . Genetic investigations of the AF synthetic mechanism have shown AF synthetic fungi contain a specific gene cluster [1,2,3,4,5,6,7,8,9]. However, many non-toxigenic strains also have this gene cluster, although these clusters may have partial deletions and/or substitutions compared to those in AF synthetic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Several food-contaminating mycotoxins including aflatoxins and ochratoxins have been identified by the International Agency for Research in Cancer (IARC) as harmful carcinogens that potently promote tumor development in several organs including the liver and kidney of mammals [1, 2]. Among the carcinogenic mycotoxins, aflatoxin B1 (AFB 1 ) has been regarded as a representative orally ingested carcinogen in humans, and is thus classified as a Group 1 carcinogen by the IARC [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the hepatocellular carcinogen aflatoxin B1 and the chemotherapeutic bikaverin [1] . These compounds are synthesized by highly regulated, large iterative multifunctional enzymes known as the type I non-reducing polyketide synthases (NR-PKSs) [2] .…”
mentioning
confidence: 99%
“…The current mix-and-match effort of PKS domains often results in a complete loss of activity, and past studies had shown that ACP incompatibility is key to such failure in combinatorial biosynthesis [1b, 15] . This work shows how we can engineer ACP to increase the compatibility of ACP and increase enzyme activity (Figure 5B), which is correlated with the crosslinking efficiency (Figure 4) and also consistent with the protein docking model (Fig.…”
mentioning
confidence: 99%